Footstrike in sprinting. An analysis - Mahoney, A. (Modern Athlete & Coach, 2014)
The author discusses the importance of feet to track and field athletes. He mentions that foot is the finest part of the body that transfers force to the ground. He focuses on the forces and physics of ground contact, and determines the amount of tonnes of forces applied by world class long jumpers. He presented video-graphic images which shows the exact foot motion during sprinting. He outlines several foot strike techniques for athletes to enhance their training skills in sprinting.